2008
DOI: 10.1136/bmj.a1786
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of shared electronic records: multi-site case study using diffusion of innovation theory

Abstract: Objective To explore the introduction of a centrally stored, shared electronic patient record (the summary care record (SCR)) in England and draw wider lessons about the implementation of large scale information technology projects in health care. Design Multi-site, mixed method case study applying utilisation focused evaluation. Setting Four early adopter sites for the SCR in Englandthree in urban areas of relative socioeconomic deprivation and the fourth in a relatively affluent rural area. Data sources and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
171
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(186 citation statements)
references
References 15 publications
5
171
0
10
Order By: Relevance
“…However, research has shown how the top-down specification-driven approach has limitations when it comes to successfully innovating information infrastructures (Ciborra et al, 2000;Greenhalgh et al, 2008;Hanseth & Ciborra, 2007;Lyytinen & Fomin, 2002). The approach does not take into account the openness of IIs, their sociotechnical complexity, or their evolutionary growing dynamics.…”
Section: Approaches To Information Infrastructure Innovationmentioning
confidence: 99%
“…However, research has shown how the top-down specification-driven approach has limitations when it comes to successfully innovating information infrastructures (Ciborra et al, 2000;Greenhalgh et al, 2008;Hanseth & Ciborra, 2007;Lyytinen & Fomin, 2002). The approach does not take into account the openness of IIs, their sociotechnical complexity, or their evolutionary growing dynamics.…”
Section: Approaches To Information Infrastructure Innovationmentioning
confidence: 99%
“…There is a substantial body of literature from Information Systems and Science and Technology Studies (STS) that discusses the outcomes, and to some extent the process, of EPR implementations at a local or national level (Brunsson et al, 2012;Davidson & Chiasson, 2005;Greenhalgh et al, 2008;Håland, 2012;Hanseth et al, 2006;Hanseth & Lundberg, 2001;Kallinikos, 2010;Jones, 2003;Lapointe & Rivard, 2005;Oborn et al, 2011;Pollock et al, 2003;Vikkelsø, 2005;Williams & Pollock, 2008). In most studies customization of EPR is presented as being confined to a single organization, the user, with other stakeholders, such as developers and suppliers, being external to it (Boulus & Bjorn, 2010;Oborn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A key determinant of successful innovation is whether the new routine associated with the innovation aligns rather than conflicts with organizational and interorganizational routines. If people are uncomfortable with the status quo and desire change, a potential innovation is more likely to be successfully adopted [16]. Alignment with routines and an understanding of the "culture of oncology," as well as flexibility to try an approach and then change to another approach as needed, were important attributes in the diffusion process for the COEs.…”
Section: Innovators and Early Adoptersmentioning
confidence: 99%